PENDIDIKAN MULTIKULTURAL DI SEKOLAH DASAR : EKSPLORASI BATIK NUSANTARA BERBASIS KEARIFAN LOKAL - Oki Kurniawan; Rossi Iskandar (Jurnal Pendidikan Dasar, 2021)
The purpose of this research is to explore the local batik Nusantara area at the level of primary school education as the initial foundation of multicultural attitude planting through formal education integrated into learning activities. Indonesia is a multicultural country with a variety of tribes, cultures, customs, languages, and religions. With such diversity, we must tie with a sense of nationalism over the ownership of the Unitary State of the Republic of Indonesia. Facing these multicultural realities, of course, the educational process must be able to optimize integrating force in the midst of the current life of globalization. However, educators and education in Indonesia, related to multicultural matters are considered as culturally sensitive. One of the efforts that can be made to improve the understanding of multiculturalism is to develop a medium that can be used as an integrating force in the life of the Indonesian nation. The most possible medium for this is batik. Batik was chosen as a media integrating force because bati has many symbols that are closely related to the local wisdom, nature, and history typical of every region in the archipelago